两栖仿生变磁力脚吸盘力学模型建立及分析 - 袁夫彩; 王立柱 (Jixie chuandong)
In order to design a biomimetic amphibian variable magnetic device that can ensure the adsorption stability and maneuverability of wall-climbing robot,the study of the device is developed.The composition and working principle of the device are introduced.The mechanically of device is analyzed,the mechanical model of avoiding overturn,slide and fall on hull is established.And the mechanical model is simulated by Matlab and is verified by experiment.So a theoretical basic for ascertaining the magnetic force of a magnetic device is provided by the study.